2018
DOI: 10.20944/preprints201804.0372.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Surface Area Mesoporous Activated Carbon from Hemp Bast Fibre Using Hydrothermal Processing

Abstract: Synthesis of activated carbon from waste biomass is of current interest towards sustainability.The properties of biomass derived activated carbon largely depends on the carbonization process. This study reports preparing extremel high surface area mesoporous activated carbon from hemp bast fibre using hydrothermal processing. Processing in hot water (390-500 o C), then activation using KOH and NaOH was investigated at different loading ratios. The described approach was found to enhance the mesoporosity (cente… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition to these, hemp has been used as a carbon source recently for many systems. In these studies various forms of hemp was used including hemp dust (Rosas, Bedia, Rodríguez-Mirasol, Cordero, research, 2008), hemp hurd (Liu et al, 2017), hemp stem (Yang et al, 2014), hemp canes (Rosas et al, 2008) and hemp fibers (Hossain et al, 2018;Mijailović et al, 2017). The hemp-derived carbon materials obtained from these studies generally showed morphologies such as activated carbon (Liu et al, 2017), activated carbon monoliths (Rosas et al, 2008) and activated carbon fibers (Mijailović et al, 2017), interconnected carbon nanosheets (Wang et al, 2013) As known, activated carbon is generally used to increase the adsorption performance of any system including gas (Liu et al, 2017), water vapor (Rosas et al, 2008), metal (Yang et al, 2014), pesticide (Vukcevic et al, 2012) etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, hemp has been used as a carbon source recently for many systems. In these studies various forms of hemp was used including hemp dust (Rosas, Bedia, Rodríguez-Mirasol, Cordero, research, 2008), hemp hurd (Liu et al, 2017), hemp stem (Yang et al, 2014), hemp canes (Rosas et al, 2008) and hemp fibers (Hossain et al, 2018;Mijailović et al, 2017). The hemp-derived carbon materials obtained from these studies generally showed morphologies such as activated carbon (Liu et al, 2017), activated carbon monoliths (Rosas et al, 2008) and activated carbon fibers (Mijailović et al, 2017), interconnected carbon nanosheets (Wang et al, 2013) As known, activated carbon is generally used to increase the adsorption performance of any system including gas (Liu et al, 2017), water vapor (Rosas et al, 2008), metal (Yang et al, 2014), pesticide (Vukcevic et al, 2012) etc.…”
Section: Introductionmentioning
confidence: 99%